2006
DOI: 10.1007/s11010-006-1400-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagen binding α2β1 and α1β1 integrins play contrasting roles in regulation of Ets-1 expression in human liver myofibroblasts

Abstract: Activation of hepatic stellate cells from quiescence to myofibroblast-like cells (MFBs) is a pivotal event in hepatic fibrogenesis. Plastic-cultured stellate cells (an established in vitro model of the activated phenotype) recultured on Matrigel revert to quiescence. In the present study we analyzed the molecular mechanism underlying this process, focusing on the effect of collagen receptors alpha(2)beta(1) and alpha(1)beta(1) integrin signaling on the expression of Ets-1 transcription factor and its target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…They are heterodimeric transmembrane proteins composed of ␣-and ␤-subunits whose ligands are matrix molecules rather than cytokines. Several integrins, disintegrins, related molecules, and their downstream effectors have been identified in stellate cells, including ␣1␤1, ␣2␤1, ␣6␤4, ␣8␤1, ␣v␤1, and ␣v␤3, and integrinlinked kinase (92,140,178,185,220,269,302,339,347,392,408,447,494,508,509,593,694,735,736,738). In particular, integrin ligands contain an arginine (Arg)-glycine (Gly)-aspartate (Asp) tripeptide sequence.…”
Section: Biology Of Membrane Receptorsmentioning
confidence: 99%
“…They are heterodimeric transmembrane proteins composed of ␣-and ␤-subunits whose ligands are matrix molecules rather than cytokines. Several integrins, disintegrins, related molecules, and their downstream effectors have been identified in stellate cells, including ␣1␤1, ␣2␤1, ␣6␤4, ␣8␤1, ␣v␤1, and ␣v␤3, and integrinlinked kinase (92,140,178,185,220,269,302,339,347,392,408,447,494,508,509,593,694,735,736,738). In particular, integrin ligands contain an arginine (Arg)-glycine (Gly)-aspartate (Asp) tripeptide sequence.…”
Section: Biology Of Membrane Receptorsmentioning
confidence: 99%
“…Changes in MMP expression are paralleled by changed expression of Ets-1 transcription factor. 103,121 The induction of MMP-13 in periodontal ligament fibroblasts is dependent on integrin a11b1. 122 The induction of MMP in collagen gel may be affected by signaling pathways downstream of integrin ligand binding.…”
mentioning
confidence: 99%
“…Several ECM genes, including type I colla- gen, are regulated by Ets-1 (61). It has been shown that elevated expression of recombinant Ets-1 has the potential to suppress the transcription of type I collagen and increase matrix degradation in transforming growth factor-␤-treated cells (28,31,47).…”
Section: Discussionmentioning
confidence: 99%